2017
DOI: 10.1002/asl.783
|View full text |Cite
|
Sign up to set email alerts
|

Delayed effect of Arctic stratospheric ozone on tropical rainfall

Abstract: The tropical precipitation has a wide effect on the tropical economics and social life. Many studies made efforts to improve the tropical precipitation forecast using tropical climate factors. This study, based on observations, found that Arctic stratospheric ozone (ASO) could exert a significant effect on the tropical precipitation, i.e. there is more (less) rainfall over the eastern Pacific and less (more) precipitation over the western Pacific when the ASO anomalies are lower (larger) than normal. It is bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 70 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…Although previous studies have shown that the ozone change in the Antarctic stratosphere can exert a significant influence on the tropospheric climate in the Southern Hemisphere (e.g., Sexton 2001;Shindell and Schmidt 2004;Son et al 2008;Polvani et al 2011;Thompson et al 2011;Keeble et al 2014), there is not similarly robust evidence of the response of the Northern Hemispheric tropospheric climate to stratospheric ozone depletion due to large interannual ozone variability and comparatively weaker ozone depletion (e.g., Thompson and Solomon 2005). Using numerical model simulations, most previous studies only found significant regional surface responses over the northern middle and high latitudes when comparing cases of extremely high and low Arctic stratospheric ozone (Cheung et al 2014;Karpechko et al 2014;Smith and Polvani 2014;Calvo et al 2015;Xie et al 2016Xie et al , 2017Harari et al 2019). One possible reason is that the dynamical variability of the Arctic stratospheric polar vortex is much larger than its Antarctic counterpart (Hu and Guan 2018;Hu et al 2019a;Mai et al 2020) and as a result Arctic stratospheric ozone depletion is less persistent than Antarctic ozone depletion (Manney et al 2011).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although previous studies have shown that the ozone change in the Antarctic stratosphere can exert a significant influence on the tropospheric climate in the Southern Hemisphere (e.g., Sexton 2001;Shindell and Schmidt 2004;Son et al 2008;Polvani et al 2011;Thompson et al 2011;Keeble et al 2014), there is not similarly robust evidence of the response of the Northern Hemispheric tropospheric climate to stratospheric ozone depletion due to large interannual ozone variability and comparatively weaker ozone depletion (e.g., Thompson and Solomon 2005). Using numerical model simulations, most previous studies only found significant regional surface responses over the northern middle and high latitudes when comparing cases of extremely high and low Arctic stratospheric ozone (Cheung et al 2014;Karpechko et al 2014;Smith and Polvani 2014;Calvo et al 2015;Xie et al 2016Xie et al , 2017Harari et al 2019). One possible reason is that the dynamical variability of the Arctic stratospheric polar vortex is much larger than its Antarctic counterpart (Hu and Guan 2018;Hu et al 2019a;Mai et al 2020) and as a result Arctic stratospheric ozone depletion is less persistent than Antarctic ozone depletion (Manney et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Stratospheric ozone depletion not only leads to a potential increase in ultraviolet radiation at the surface that is harmful for human health and to terrestrial and aquatic ecosystems, but also has important impacts on atmospheric temperature and circulation through ozone Supplemental information related to this paper is available at the Journals Online website: https://doi.org/10.1175/JCLI-D-19-0647.s1. radiative heating (e.g., Ramaswamy et al 1996;Forster and Shine 1997;Shindell et al 1999;Tian and Chipperfield 2005;Xie et al 2008;Wang et al 2014;Nowack et al 2015;Garfinkel 2017). Although previous studies have shown that the ozone change in the Antarctic stratosphere can exert a significant influence on the tropospheric climate in the Southern Hemisphere (e.g., Sexton 2001;Shindell and Schmidt 2004;Son et al 2008;Polvani et al 2011;Thompson et al 2011;Keeble et al 2014), there is not similarly robust evidence of the response of the Northern Hemispheric tropospheric climate to stratospheric ozone depletion due to large interannual ozone variability and comparatively weaker ozone depletion (e.g., Thompson and Solomon 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equatorial waves influence atmospheric oscillations on pressure, air temperature, humidity, convection, and wind, in which the more magnitude oscillations can directly affect weather in the tropics (Ling et al, 2019;Türkeş and Erlat, 2018;Ying and Zhang, 2017), such as the intensity and onset of precipitation in the tropics (Cavalcanti et al, 2017;Dias et al, 2018;Kim and Kim, 2016;Lubis and Jacobi, 2015;Niang et al, 2017;Sakaeda et al, 2020;Steptoe et al, 2018;Xie et al, 2017;Zhang et al, 2018). Equatorial waves theory developed by Matsuno (1966) has only been confirmed by Wheeler and Kiladis (1999) as WK99.…”
Section: Introductionmentioning
confidence: 99%
“…Based on observations and simulations, it is found that the northern stratospheric circulation anomalies induced by ASO radiative anomalies could cause North Pacific SST anomalies (Victoria Mode anomalies) 24 , 25 . The SST anomalies link to the North Pacific circulation that in turn influences El Niño–Southern Oscillation (ENSO) 24 and tropical rainfall 26 .…”
Section: Introductionmentioning
confidence: 99%